Exploring musical self-efficacy and performance anxiety in young violin learners: insights from mainland China - Jiayi Ou; Chao Qin (Frontiers in Psychology)
IntroductionMusic self-efficacy (MSE) and music performance anxiety (MPA) are critical issues in music education. This study examines MSE, including both music learning self-efficacy (MLSE) and music performance self-efficacy (MPSE), as well as MPA, among undergraduate violin students in mainland China.MethodsData were collected via an online survey distributed to students from 11 music conservatories, resulting in 254 valid responses.Results and discussionThe results revealed moderate levels of MLSE and MPSE, with no significant gender differences. Differences were observed across academic years, with lower-year students reporting higher MLSE and MPSE than upper-year students. Conservatory level also influenced MLSE and MPSE, with A-level students scoring higher than B- and C-level students. MPA levels were generally high, but no gender or academic year differences were observed. However, a U-shaped pattern of MPA across conservatory levels was identified, with A- and C-level students experiencing higher anxiety than B-level students. Notably, MLSE was positively associated with MPA, while MPSE showed a negative association, suggesting that the two types of self-efficacy play divergent roles in MPA. These findings indicate that while MLSE and MPSE are moderately correlated, they differentially influence violin students’ MPA.